Experimental Model оf a Multibeam Device for Observation in Radio Light - Dmitriev, A. S.; Petrosyan, M. M.; Ryzhov, A. I. (Technical physics letters, 2021)
The possibility of creating an analog of the biological eye in the radio range for observing the surrounding space in artificial radio light is considered. As in the biological prototype, the analog has a system of sensitive elements (retina), a lens-type focusing element and a set of directional antennas, which are used for the primary reception of noiselike ultrawideband radiation. An experimental device of the considered type is designed and the operability of the proposed technical solution is demonstrated.